Perlindungan Hukum Terhadap Merek Terdaftar Industri UMKM di Sumatera Barat - Nesia Hani Putri; Muni Ayu Lestari; Mona Lisa; Annisaa’ jawaad (CV. ITTC INDONESIA, 2023)
How is legal protection for brands in West Sumatra? This research aims to find out the extent to which West Sumatra MSMEs receive legal protection for brands and the extent to which West Sumatra MSMEs have registered their brands. This research uses the method that will be used in this paper, namely a sociological or empirical juridical approach. Based on the results, many MSME brands in West Sumatra do not register their brands so they do not receive business legal protection for their brands